THE ROLE OF THE «GRAND SCHOOLS» AND THE «GRAND CORPS» AS RECRUITMENT CHANNELS FOR FRENCH MINISTERS - I. A. Zarankin (Vestnik MGIMO-Universiteta)
The recruitment of ministers among high-ranking officials, who studied in the «grand schools» and worked in the «grand corps», is one of the typical traits of the Fifth republic. This is a consequence of the traditional interpenetration of French administrative and political elites. However, there is no common view on the actual role of these institutions in the ministers’ recruitment. So, the objective of this paper is to clarify this issue. For this purpose we analyze career trajectories of French ministers from 1981 till 2016. The data on each government include shares of ministers, who passed through the «grand schools» and the «grand corps». The article shows that nowadays the number of ministers with such an experience has decreased. Most government members are professional politicians, who have significant electoral experience and occupy high-ranking party positions. Today there are political parties, not the «grand schools» and the «grand corps», that are the main channels of the ministers’ recruitment. The professionalization of politics and reinforcement of the role of parties in the French political system are the most crucial factors of this tendency. The transformation of gaullists into liberals and conduction of the liberal economic policy, instead of the dirigist one, also contributed to replacement of officials by representatives of the private sector. Despite the fact that political parties serve as a main channel of the ministers’ recruitment, they face internal problems. The future role of political parties in the recruitment will depend on their ability to deal with these challenges.